The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1002/hup.927
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lorazepam on visual perceptual abilities

Abstract: Acute administration of lorazepam, in a dose that impaired episodic memory, selectively affected different visual perceptual abilities before and after controlling for sedation. Central executive demands and sedation did not account for results, so impairment in the Identical Pictures task may be attributed to lorazepam's visual processing alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
(100 reference statements)
1
6
0
2
Order By: Relevance
“…The presence of LOR effects at this dosage on these domains is consistent with previous reports of acute LOR exposure [6,16].…”
Section: Discussionsupporting
confidence: 91%
“…The presence of LOR effects at this dosage on these domains is consistent with previous reports of acute LOR exposure [6,16].…”
Section: Discussionsupporting
confidence: 91%
“…The advantage in memorizing visual stimuli possibly owe to improvement in visual processing (see Furey et al, 2008a) elicited by this drug and observed as a shortening of IT. It also may relate to the improvement found in executive mechanisms because even simple visuospatial tasks seem to heavily implicate central executive functioning (Baddeley et al, 1999;Miyake et al, 2001;Pompéia et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Studies of DSST performance relative to placebo have shown effect sizes (Cohen’s d ) of 0.25–0.5 for diphenhydramine (Roth et al, 1987) and lorazepam (Pompeia et al, 2008), and 0.68 in people whose blood alcohol concentration is 0.09% (Mattila and Mattila-Evenden, 1997; national guidelines usually stipulate an upper threshold of either 0.05 or 0.08%; ). Importantly, while the effects of these agents cease once the drug effects wear off, the effects of cognitive dysfunction in chronic MDD are far more persistent.…”
Section: Discussionmentioning
confidence: 99%